Lithium‐Salt‐Containing High‐Molecular‐Weight Polystyrene‐block‐Polyethylene Oxide Block Copolymer Films. Issue 13 (10th August 2015) - Metwalli, Ezzeldin; Rasool, Majid; Brunner, Simon; Müller‐Buschbaum, Peter
Abstract Ionic conductivity in relation to the morphology of lithium‐doped high‐molecular‐weight polystyrene‐block‐polyethylene oxide (PS‐b‐PEO) diblock copolymer films was investigated as solid‐state membranes for lithium‐ion batteries. The tendency of the polyethylene (PEO) block to crystallize was highly suppressed by increasing both the salt‐doping level and the temperature. The PEO crystallites completely vanished at a salt‐doping ratio of Li/EO>0.08, at which the PEO segments were hindered from entering the crystalline unit of the PEO chain. A kinetically trapped lamella morphology of PS‐b‐PEO was observed, due to PEO crystallization. The increase in the lamella spacing with increasing salt concentration was attributed to the conformation of the PEO chain rather than the volume contribution of the salt or the previously reported increase in the effective interaction parameter. Upon loading the salt, the PEO chains changed from a compact/highly folded conformation to an amorphous/expanded‐like conformation. The ionic conductivity was enhanced by amorphization of PEO and thereby the mobility of the PEO blocks increased upon increasing the salt‐doping level.